Pengaruh Intensitas Modal Dan Tanggung Jawab Sosial Perusahaan Terhadap Penghindaran Pajak Dengan Ukuran Perusahaan Sebagai Variabel Pemoderasi - Tarnaba, Rama Rachman; Tumirin, Tumirin (Jurnal Akuntansi Manado (JAIM), 2024)
This study aims to find out the impact of capital intensity and social responsibility on tax avoidance, with company size as a moderation variable. The study population included manufacturing companies listed on the IDX from 2019 to 2022. Using the purposive sampling method, the study analyzed 32 manufacturing companies over a four-year period, resulting in 128 observations. The test results stated, where capital intensity had a negative effect on tax avoidance, while social responsibility had a significant positive effect on tax avoidance. Based on the results of a moderated regression analysis where company size does not significantly moderate the relationship between capital intensity and social responsibility in tax avoidance.